2021
DOI: 10.1097/j.pain.0000000000002223
|View full text |Cite
|
Sign up to set email alerts
|

Spinal nociceptive sensitization and plasma palmitoylethanolamide levels during experimentally induced migraine attacks

Abstract: Migraine pathophysiology has been suggested to include dysregulation of the endocannabinoid system (ES). We simultaneously evaluated plasma anandamide (AEA) and palmitoylethanolamide (PEA) levels and spinal sensitization in a validated human model of migraine based on systemic nitroglycerin (NTG) administration. Twenty-four subjects with episodic migraine (MIG) and 19 healthy controls (HC) underwent blood sampling and investigation of nociceptive withdrawal reflex thresholds (RTh: single-stimulus threshold; TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
(76 reference statements)
1
11
0
Order By: Relevance
“…Similar findings have also been reported with auditory evoked potentials [36] and with the evaluation of nociceptive withdrawal reflex [39] and the blink reflex [40], to suggest that the migraine brain is characterized by a lack of habituation of responses evoked by repeated stimuli. Finally, it was demonstrated [41] that responses to peripheral stimulation were reduced in patients with migraine.…”
Section: Pathophysiologysupporting
confidence: 83%
“…Similar findings have also been reported with auditory evoked potentials [36] and with the evaluation of nociceptive withdrawal reflex [39] and the blink reflex [40], to suggest that the migraine brain is characterized by a lack of habituation of responses evoked by repeated stimuli. Finally, it was demonstrated [41] that responses to peripheral stimulation were reduced in patients with migraine.…”
Section: Pathophysiologysupporting
confidence: 83%
“…AEA levels increased in both EM patients and healthy controls, whereas PEA increased only in migraine patients, regardless of whether or not a migraine attack was reported. The increased PEA in migraineurs vs. healthy controls presumably reflects migraine-specific mechanisms [ 37 ]. No clinical trials on compounds capable of modulating the ECS (such as FAAH/MAGL inhibitors) are currently available for migraine.…”
Section: Resultsmentioning
confidence: 99%
“…The full description of the study population and experimental design is reported in the main study [ 8 ]. Briefly, our sample comprised 24 patients with a diagnosis of episodic migraine (MIG group) and a group of 19 healthy controls (HC group).…”
Section: Methodsmentioning
confidence: 99%